Transnational Engagements of Mirpuri-British Emigrants in Mirpur, AJK - Siddique, Muhammad; Bhatti, Dr. Ilyas (University of Wah Journal of Social Sciences, 2022)
This research paper looks into transnational engagements of British emigrants in Mirpur AJK. The three generation i.e., first generation, 1.5th generation and second generations have been investigated in terms of the frequency of homeland visits, remittances sending, wish for permanent return, homeland political engagement, homeland spiritual engagements and sending for charitable activities. The results show that though emigrants support various causes through various modes and motives; however, engagements with homeland prevails across generations. The study reveals that emigrants are embedded in the social structure of homeland and bonded with homeland though various set of connections.